Body Weight Variability Increases Dementia Risk Among Older Adults: A Nationwide Population-Based Cohort Study - Roh, Eun; Hwang, Soon Young; Kim, Jung A.; Lee, You-Bin; Hong, So-hyeon; Kim, Nam Hoon; Seo, Ji A.; Kim, Sin Gon; Kim, Nan Hee; Choi, Kyung Mook; Baik, Sei Hyun; Yoo, Hye Jin (Frontiers in Endocrinology, 2020)
Background: Recent growing evidences suggest that body weight (Bwt) variability, a repeated loss and regain of weight within a specific period, causes metabolic disturbances and can be a marker for poor homeostasis. Although there have been many studies about the association between Bwt variability and various health status, its association with the incidence of dementia among elderly people has not been examined. Methods: We performed a retrospective elderly cohort study from 19,987 participants with mean age 73 years old in the Korean National Health Insurance Service. We examined the risk of incident dementia, including Alzheimer’s dementia and vascular dementia, according to the quartile of Bwt variability, represented as coefficient of variation (Bwt-CV), SD (Bwt-SD), and variability independent of the mean (Bwt-VIM). Results: In fully adjusted model, the group with the highest Bwt variability (Bwt-VIM Q4) showed an increased risk of all-cause dementia (hazard ratio [HR] 1.39, 95% confidence interval [CI] 1.206–1.603) and Alzheimer’s dementia (HR 1.46, CI 1.240–1.724) compared to the lowest quartile (Bwt-VIM Q1). We also found that subjects with the highest Bwt variability (Q4) and underweight BMI had a significantly increased risk of developing dementia (HR 1.994, 95% CI 1.302-3.054), while subjects with low Bwt variability (Q1 and Q2) and obese BMI had decreased risk of dementia (HR 0.664, 95% CI 0.505-0.872 and HR 0.648, 95% CI 0.493-0.852, respectively) compared to reference group (lowest Bwt variability (Q1) with normal baseline BMI). The effect of Bwt variability on the incidence of dementia was more prominent in subjects <75 years old and abnormal BMI groups (P for interaction < 0.05). Conclusion: The present study revealed that high Bwt variability was associated with an increased risk of dementia in the elderly.